An unsymmetrical pentacene derivative with ambipolar behavior in organic thin-film transistors - Tykwinski, Rik; Etschel, Sebastian; Halik, Marcus; Jäger, Christof; Clark, Timothy; Margraf, Johannes; Waterloo, Andreas; Hampel, Frank; Yousefi Amin, Atefeh (Chemical Communications, 2013)
Three new unsymmetrical anthracenyl-pentacene derivatives have been synthesized, characterized using X-ray crystallography, and used as semiconductors in OTFTs. For one derivative, ambipolar charge carrier transport was observed with a hole mobility of 0.2 cm V s and an electron mobility of 0.03 cm V s. © 2013 The Royal Society of Chemistry.